NORMALISASI HUBUNGAN DIPLOMATIK TURKI DAN RUSIA PASCA PENEMBAKAN PESAWAT SU-24 RUSIA OLEH PASUKAN UDARA TURKI PADA TAHUN 2015-2016 - Ratna Pramesti, Ni Nyoman Ayu; Kumala Dewi, Putu Ratih; Widya Nugraha, A.A. Bagus Surya (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL), 2019)
ABSTRACT The shot down incident of Russian Su-24 aircraft by the Turkish Air Force on 24th November 2015 has suddenly disrupted the diplomatic relations between the countries. As the response of the incident, Russia imposed economic sanctions on Turkey that affected Turkish capabilities to pursue their national interest. Approximately 7 months after the incident, Turkey made an effort to normalize their diplomatic relations with Russia, to reconcile their ties and restore the cooperation between the countries. The normalization finally took place with the meeting of the two country’s leaders in St. Petersburg, Russia, on 9th August 2016. The aim of this research is to describe the factors that encouraged Turkey to normalize their diplomatic relations with Russia after the shot down incident of Russian Su-24 aircraft that took the locus on 2015-2016. This research was analyzed by Foreign Policy Decision Making (FPDM) concept, particularly on the Domestic and International Factors. Key words: Normalization, Diplomatic Relation, Turkey, Russia